XEW 2.0: big data analytics tool based on swarm intelligence. (16th April 2021) - Bouhafer, Fadwa; Haddadi, Anass El; Heyouni, Mohammed; Ali, Ouafaa Ben
Nowadays, data is a golden capital for any business organisation that wants to improve their business. The big organisations and the most reputed ones do not only think to collect data, but they make continuous efforts to use this data for efficient decision-making. Data visualisation plays a crucial importance in big data analysis. The existence of various data visualisation methods can be confusing for users to choose the most appropriate. In this paper, we present the big data analytics tool XEW 2.0 based on swarm intelligence, especially the ant colony optimisation. XEW 2.0 design is based on a detailed study of data visualisation. This study presents a guide for choosing data visualisation methods, and how the traditional methods are improved to meet the big data visualisations need.